Preparation and Characterization of Goat Hoof Keratin/Gelatin/Sodium Alginate Base Biofilm for Tissue Engineering Application. Issue 202 (13th October 2019) - Kumar, S. Logesh; Anandhavelu, S.; Swathy, M.
Abstract: The formation of keratin (KE) based tissue regenerative substitute from waste goat hoof source, integrated with gelatin (GE) and sodium alginate (AL) for improved biological and mechanical properties. In this study, biofilm samples prepared using solvent casting method showed improved physiochemical and morphological properties. The biofilm was characterized by FTIR spectra, XRD spectra, TG-DTA curve and SEM analysis. During in-vitro swelling and antimicrobial study, the biofilm exhibits good swelling and antibacterial property. The biofilm also reveals excellent biocompatibility in fibroblast cell lines. KE based biofilm has good cell binding nature and used as rapid tissue growth promoter in tissue engineering applications.